The Antimicrobial Potency of Mesoporous Silica Nanoparticles Loaded with Melissa officinalis Extract - Gabriela Petrișor; Ludmila Motelica; Roxana Doina Trușcǎ; Andreea-Luiza Mȋrț; Gabriel Vasilievici; Justinian-Andrei Tomescu; Cristina Manea; Andreea Ștefania Dumbravǎ; Viorica Maria Corbu; Irina Gheorghe-Barbu; Denisa Ficai; Ovidiu-Cristian Oprea; et al. (MDPI AG, 2024)
Melissa officinalis is an important medicinal plant that is used and studied intensively due to its numerous pharmacological effects. This plant has numerous active compounds with biomedical potential; some are volatile, while others are sensitive to heat or oxygen. Therefore, to increase stability and prolong biological activities, the natural extract can be loaded into various nanostructured systems. In this study, different loading systems were obtained from mesoporous silica, like Mobile Composition of Matter family (MCM) with a hexagonal (MCM-41) or cubic (MCM-48) pore structure, simple or functionalized with amino groups (using 3-aminopropyl) such as triethoxysilane (APTES). Thus, the four materials were characterized from morphological and structural points of view by scanning electron microscopy, a BET analysis with adsorption-desorption isotherms, Fourier-transform infrared spectroscopy (FTIR) and a thermogravimetric analysis coupled with differential scanning calorimetry. Natural extract from Melissa officinalis was concentrated and analyzed by High-Performance Liquid Chromatography to identify the polyphenolic compounds. The obtained materials were tested against Gram-negative bacteria and yeasts and against both reference strains and clinical strains belonging to Gram-positive bacteria that were previously isolated from intra-hospital infections. The highest antimicrobial efficiency was found against Gram-positive and fungal strains. Good activity was also recorded against methicillin-resistant S. aureus, the Melissa officinalis extract inhibiting the production of various virulence factors.